Best Bilinear Approximations for the Classes of Functions of Many Variables - Romanyuk, A. S.; Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We obtain upper bounds for the values of the best bilinear approximations in the Lebesgue spaces of periodic functions of many variables from the Besov-type classes. In special cases, it is shown that these bounds are order exact.